Biochemical markers for resistance and susceptibility to fusarium wilt disease in bananas. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2006)
Fusarium wilt caused by the fungus, Fusarium oxysporum f.sp. cubense is a major factor limiting commercial banana production in Malaysia Reid evaluation of banana plants for Fusarium wilt disease has nat been effective as the infection period is slow and other variables such as distribution of inoculum concentration is difficult to control.